(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
A large class of real-world problems, arising in the administrative - organizational systems is connected with the attestation of the academic staff in accordance with predefined and linguistically described evaluation criteria. Such problems are solved in the circumstances of uncertainties of different types. The process of interpretation goes together with some ambiguity and inaccuracy due to the subjective interpretation of the criteria by experts. The Fuzzy Set theory provides a convenient apparatus for formalization and creation of new intelligent decision-making methods, based on analysis and processing of the expert knowledge. This paper offers a method of fuzzy modelling of the problem of scientific and pedagogical staff attestation which gives the possibility of an adequate interpretation of the attestation results. The method can be implemented programmatically and can be incorporated in the systems of education quality management.